New miniature chitosan diaphragm-based fabry-perot interferometric sensor for medical applications - Goh, Siew Kee. (2009)
Miniature sensors are highly attractive for various applications, especially when space is restricted, such as in invasive blood pressure measurement. Fiber-optic sensors offer excellent solution due to their small size and biocompatibility. In this project, a chitosan diaphragm-based miniature fiber-optic Fabry-Perot sensor was developed. Fabrication of this sensor only required simple steps like cleaving, arc fusion splicing and diaphragm formation through surface tension. In addition, it allowed thinner diaphragm to be fabricated and eliminated the hazard of wet etching. Demodulation was carried out to examine air cavity length change of the sensor under pressure change. Low Young’s Modulus of 2283 MPa for unmodified chitosan film allowed the sensor to achieve high pressure sensitivity of 1.35 µm/psi in static pressure measurement in the pressure range of 0 psi to 5 psi. For acoustic pressure measurement, it was capable of detecting real-time response from 20 Hz to 20 kHz with a high sensitivity of -16dB. However, signal-to-noise ratio was unsatisfactory but this could be improved through signal processing in the future. In conclusion, an improved miniature extrinsic Fabry-Perot interferometric sensor was developed in this project. High sensitivity in the low pressure region and wide frequency range makes it a good candidate in biomedical application, such as in real-time invasive blood pressure measurement and in non-invasive blood pressure measurement through the detection of korotkoff sounds.